Heregulin controls ERα and HER2 signaling in mammospheres of ERα-positive breast cancer cells and interferes with the efficacy of molecular targeted therapy. Issue 201 (July 2020) - Fukui, Fumiyo; Hayashi, Shin-ichi; Yamaguchi, Yuri
Highlights: Heregulin-1β (HRG) decreased ERα and inversely increased HER -family mRNA expression in ERα-positive breast cancer cells. HRG expression increased cancer stem cell-like characteristics in ERα-positive breast cancer cells. HRG attenuated the reduction in cell growth of ERα-positive breast cancer cells following mTOR inhibitor treatment. Abstract: Estrogen receptor (ER)α and the human epidermal growth factor receptor (HER) family are inversely expressed in ERα-positive cancer in association with resistance to hormonal therapy, but the mechanism underlying their relationship remains unknown. We analyzed the effect of HER family ligands on the expression of ER and the HER family in ERα-positive MCF-7 and T47D breast cancer cell lines in 3D spheroid culture. Here, we demonstrated for the first time that heregulin-1β (HRG), a HER3 and HER4 ligand, most effectively regulated ER/HER family expression by decreasing ERα mRNA expression and increasing HER family mRNA expression. HRG treatment attenuated fulvestrant-mediated growth inhibition, and promoted the migration of MCF-7 cells. Moreover, HRG increased the CD44 + /CD24 − cell fraction and side population cells, both of which are recognized as prospective breast cancer stem cell markers. HRG activated both phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) and mitogen-activated protein kinase (MAPK) pathways. Inhibitors of these pathways reduced the growth of MCF-7 cells, but the addition of HRG has different effects on these pathways. HRG blocked the inhibitory effect of mTOR inhibitors, such as rapamycin and everolimus, on cell growth but not that of a PI3K inhibitor. Furthermore, HRG slightly decreased the inhibitory effect of an AKT inhibitor on cell growth. In contrast, HRG enhanced the MEK inhibitor-induced inhibition of cell growth. These findings suggest that HRG-stimulated signaling pathways allow ERα-positive breast cancer cells to escape from growth inhibition caused by everolimus, via MAPK signaling and/or other signaling pathways. Everolimus improves progression-free survival in combination with exemestane as second-line therapy for metastatic hormone receptor-positive breast cancer. Our study suggests that HRG is a novel target for ERα-positive breast cancer therapy.